Hubungan Pengetahuan Ibu Hamil Tentang Gizi Dengan Nutrisi Selama Kehamilan Di Wilayah Kerja Puskesmas Mapaddegat - Hidayah Afnas, Nur; Elwitri, Elwitri Silvia; Sri Rahmayeni, Lola (Universitas Sumatera Barat, 2024)
The nutritional status of pregnant women has a direct impact on the course of pregnancy and the baby that will be born. Malnutrition that occurs in the early months of pregnancy affects the development and capacity of the embryo to survive. Poor nutrition in late pregnancy affects growth. The aim of the research is to determine the relationship between pregnant women's knowledge about nutrition and nutrition during pregnancy in the Mapaddegat Community Health Center working area. This type of research uses an observational method with a cross sectional approach, which was carried out at the Mapaddegat Health Center in September 2023 - April 2024. The population in this study were all pregnant women in the Mapaddegat Health Center working area. The total population was 208 people with a sample of 31 pregnant women. Data analysis techniques use SPSS with dependent and dependent variables with univariate and bivariate analysis. The research results showed that most of the respondents' characteristics based on age were 20 - 35 years, 23 people (74.2%), most of the education was high school, 23 people (74.2%), and most of the jobs were housewives, 21 people (67, 7%). Nutritional status based on BMI of 18 people (58.1%). More than half of the nutritional status based on LILA of respondents was not KEK, 19 people (61.3%). The conclusion is that there is a relationship between age and Knowledge about Nutrition of Pregnant Women pValue = 0.205, Education pValue = 0.001, Occupation pValue- 0.001, nutritional status pValue= 0.034. It is hoped that respondents will be able to increase the fulfillment of nutritional needs during pregnancy, and for health workers to always provide health education to pregnant women regarding pregnancy nutritional problems.